2018
DOI: 10.1017/s0003055418000862
|View full text |Cite
|
Sign up to set email alerts
|

Family Matters? Voting Behavior in Households with Criminal Justice Contact

Abstract: Contact with the criminal legal system has been shown to reduce individuals’ political participation, but its effect on friends and family members is less clear. Do people who see loved ones arrested or incarcerated become mobilized to change the system, or do they withdraw from political life? I address this question using administrative data from one large county, identifying registered voters who live with someone facing misdemeanor charges. Court records and vote histories allow me to accurately measure pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(33 citation statements)
references
References 20 publications
0
33
0
Order By: Relevance
“…A large body of research in political science has documented that involuntary interactions with criminal justice institutions are politically demobilizing and dramatic moments of negative political socialization. For example, the finding that arrest and incarceration decreases voting among individuals, family members connected to the justice-involved, and communities where they reside has appeared across a range of studies, including those that measure changes in voting behavior after an arrest or conviction across multiple waves, in non-parametric analyses that match those who had been incarcerated with those who would be in the future, and in studies that use random assignment to less and more punitive judges to estimate causal effects of brief jail confinement (Burch 2013; Gerber et al 2017; Lerman and Weaver 2014a; Manza and Uggen 2008; Weaver and Lerman 2010; White 2019a; 2019b; c.f. Anoll and Israel-Trummel 2019; Walker 2014).…”
Section: A Strategy Of Community Control In the Face Of Police Oppresmentioning
confidence: 99%
“…A large body of research in political science has documented that involuntary interactions with criminal justice institutions are politically demobilizing and dramatic moments of negative political socialization. For example, the finding that arrest and incarceration decreases voting among individuals, family members connected to the justice-involved, and communities where they reside has appeared across a range of studies, including those that measure changes in voting behavior after an arrest or conviction across multiple waves, in non-parametric analyses that match those who had been incarcerated with those who would be in the future, and in studies that use random assignment to less and more punitive judges to estimate causal effects of brief jail confinement (Burch 2013; Gerber et al 2017; Lerman and Weaver 2014a; Manza and Uggen 2008; Weaver and Lerman 2010; White 2019a; 2019b; c.f. Anoll and Israel-Trummel 2019; Walker 2014).…”
Section: A Strategy Of Community Control In the Face Of Police Oppresmentioning
confidence: 99%
“…Research examining the civic consequences of having a relational connection to a custodial citizen finds that the policy feedback effects of contact identified by Lerman and Weaver (2014a) spill over to those who experience the system vicariously, albeit in sometimes unexpected ways (Anoll and Israel-Trummel 2019; Mondak et al 2017; Lee, Porter, and Comfort 2014; Walker 2014; 2020). While scholars largely draw on survey data to identify people with proximal criminal legal connections, the use of administrative records to identify these same people is one of the most exciting developments in this line of inquiry (White 2018).…”
Section: How Marginalized People View the Criminal Legal Systemmentioning
confidence: 99%
“…Serving even short sentences in prison or jail is also negatively associated with voter registration and voting (Bobo & Thompson, 2006). In addition, individuals that experience family member conviction or incarceration similarly experience a demobilization effect (White, 2019b). White (2016) found that experiencing familial incarceration reduced turnout by 15 percent in the following election cycle.…”
Section: Carceral Contact and Political Participationmentioning
confidence: 99%